Tetragonal pencil-like VO2(R) as electrode materials for high-performance redox activities. Issue 5 (April 2016) - Mjejri, I.; Etteyeb, N.; Somrani, S.; Sediri, F.
Abstract: Pencil-like tetragonal vanadium dioxide has been synthesized via one-step hydrothermal treatment. The compounds were analyzed through X-ray powder diffraction; scanning electron microscope and X-ray photoelectron spectroscopy (XPS). The optical properties of the as-synthesized material were studied by UV–visible diffuse reflection spectroscopy and room temperature photoluminescence. Thin films of VO2 (R) deposited on ITO substrates were electrochemically characterized by cyclic voltammetry (CV). The voltammograms show a reversible redox behavior with a doping/dedoping process corresponding to reversible cation intercalation/de-intercalation into the crystal lattice of the pencil. This process is easier in propylene carbonate than in aqueous solvent. It is also easier for the small Li + cation than larger ones, Na + and K + . This is attributed to a probable presence of one tunnel cavities in the structure of VO2 (R). The good electrochemical property of the VO2 (R) is attributed to its unique ultralong nanopencils structure with a good structural stability.